Entrapment of a micro-guidewire during stenting of basilar stenosis. (1st August 2013) - Ma, Ning; Liu, Lian; Wang, Tie-Jun; Xu, Xiao-Tong; Miao, Zhong-Rong
Abstract : Entrapment of a microwire related to intracranial endovascular therapy is an uncommon complication. A 64-year-old man with symptomatic basilar artery stenosis was treated with stenting. A 300 cm Synchro microwire became trapped in the P1 segment of the left posterior cerebral artery during the procedure. The decision was made to leave the microwire in place, considering that aggressive retrieval procedures could cause injury to the cerebral vasculature. The entrapped microwire was later inadvertently dislocated and removed while pulling the microwire back into the femoral artery with a looped catheter from the left femoral access. This demonstrates that, although entrapment of a microwire during endovascular therapy is a rare event, an optimal salvage technique needs to be explored further.